Contribution indicators of work stress and employee organizational commitments case study - Tuty Sariwulan; Muhammad Calvin Capnary; Iskandar Agung (Verslas: Teorija ir praktika / Business: Theory and Practice, 2019)
This study aims to determine the contribution of work stress indicators as exogenous variables and organizational commitment as endogenous variables consisting of subvariable affective, continuance, and normative commitments. The sample of respondents in the study were 150 people with analysis using the assistance of the lisrel 8.80 program. Based on the research it was found that exogenous variables affect endogenous variables. In addition, it was also found that leadership and open information indicators in companies were ranked first and second in contributing to work stress. In affective commitment are indicators of level of income and job satisfaction. In continuity of commitment is an indicator of work passion and hope for improvement in life. In normative commitment are indicators of the implementation of the reward system and work time. Based on this, it is recommended that companies need to implement appropriate and effective strategies to overcome employee stress problems by developing leadership patterns that are more democratic, transparent, egalitarian; involves employee participation in decision making; career certainty; consistently applying the reward system; and others. This will be an entry point for creating enthusiasm, job satisfaction, loyalty, and employee performance that will increase the company's productivity and progress.
Keywords: J24; 650; work stress; commitment organizational; impact; contribution; indicators